2021
DOI: 10.1111/tri.13887
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate therapy after liver transplant improves bone mineral density and reduces fracture rates: an updated systematic review and meta‐analysis

Abstract: Summary To investigate the efficacy of bisphosphonates and compare oral and IV formulations on bone mineral density (BMD) and fracture incidence in post‐orthotopic liver transplant (OLT) patients. Electronic databases were searched, and six RCTs and three cohort studies were included out of 711 articles. Main outcomes included post‐OLT BMD changes, fracture incidence, and treatment adverse reactions. Pairwise meta‐analysis was conducted for binary and continuous outcomes, while pooled fracture incidence utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Patients who developed osteoporotic fractures after LDLT had higher baseline OPG, lower baseline RANKL and a higher OPG/RANKL ratio. A recent meta-analysis suggested that bisphosphonate therapy could reduce fracture rates in liver transplant recipients, but the fracture incidence was still as high as 6.6% even in the bisphosphonate group [30]. Based on our findings and published studies, we hypothesize that a relatively low but not extremely low systemic osteoclast activity level may be optimal to prevent osteoporotic fractures in LDLT recipients.…”
Section: Discussionsupporting
confidence: 62%
“…Patients who developed osteoporotic fractures after LDLT had higher baseline OPG, lower baseline RANKL and a higher OPG/RANKL ratio. A recent meta-analysis suggested that bisphosphonate therapy could reduce fracture rates in liver transplant recipients, but the fracture incidence was still as high as 6.6% even in the bisphosphonate group [30]. Based on our findings and published studies, we hypothesize that a relatively low but not extremely low systemic osteoclast activity level may be optimal to prevent osteoporotic fractures in LDLT recipients.…”
Section: Discussionsupporting
confidence: 62%
“…Chronic obstructive liver disease may interfere with vitamin D metabolism, leading to decreased uptake of vitamin D. In addition, cirrhosis has been shown to impair 25-hydroxylation of vitamin D, consequently resulting in significantly depressed levels of 25-hydroxyvitamin D3 [ 23 ]. Previous studies have reported that prophylactic bisphosphonate treatment is effective in preventing bone loss and fractures in liver transplant recipients [ 24 , 25 ]. In the present study, we found that the use of bone protective medications including bisphosphonates, vitamin D supplements and calcium supplements did not have a beneficial effect on decreasing the risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic osteodystrophy is a relevant complication in patients with advanced liver disease and transplant recipients, with fractures and osteoporosis being more common in the first year after transplant, corresponding to the greatest bone loss period. [6][7][8][9][10] The assessment of the bone bases is carried out using imaging tests, such as a panoramic x-ray of the jaw, which is a routine complementary examination in dental care. 10 The analysis of the mandibular córtex endosteum quality and the analysis of this same cortex at the level of the mental foramen are valuable techniques for evaluating bone signs of low bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in bone metabolism may also occur as liver disease progresses. Hepatic osteodystrophy is a relevant complication in patients with advanced liver disease and transplant recipients, with fractures and osteoporosis being more common in the first year after transplant, corresponding to the greatest bone loss period 6–10 …”
Section: Introductionmentioning
confidence: 99%